2015
DOI: 10.1002/mabi.201500014
|View full text |Cite
|
Sign up to set email alerts
|

Highly Porous Gelatin Reinforced 3D Scaffolds for Articular Cartilage Regeneration

Abstract: 3D highly porous (93% total porosity) gelatin scaffolds were prepared according to a novel, simple method, which implies gelatin foaming, gelification, soaking into ethanol and successive freeze-drying. Reinforcement of the as-prepared scaffolds (GEL) was performed through immersion in aqueous solutions at different gelatin concentrations. Reinforcement solutions with and without genipin addition allowed to prepare two series of samples:cross-linked and uncross-linked samples, respectively. The amount of gelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 30 publications
2
20
0
2
Order By: Relevance
“…The equilibrium water uptake ability (WUA) was determined after immersion of the preweighted dry samples in phosphate buffered saline (PBS) 0.1 m , pH 7.4 at 37 °C for 20 s. The weight of wet samples was measured after PBS excess removal. Then, the water uptake ability was calculated according to the following equationWUA=WnormalwWnormaldWnormaldwhere W w and W d represent the weight of wet and dry sample, respectively . The process was repeated in triplicate and data were reported as mean and standard deviation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The equilibrium water uptake ability (WUA) was determined after immersion of the preweighted dry samples in phosphate buffered saline (PBS) 0.1 m , pH 7.4 at 37 °C for 20 s. The weight of wet samples was measured after PBS excess removal. Then, the water uptake ability was calculated according to the following equationWUA=WnormalwWnormaldWnormaldwhere W w and W d represent the weight of wet and dry sample, respectively . The process was repeated in triplicate and data were reported as mean and standard deviation.…”
Section: Methodsmentioning
confidence: 99%
“…[1,2] Its beneficial influence on bone remodeling has www.advancedsciencenews.com www.mbs-journal.de of Sr substitution in SrHA utilized for the preparation of the scaffolds was based on the results of previous in vitro studies, which demonstrated that Sr substitution of a few atom% is able to influence bone cells behavior reducing osteoclast activity and promoting osteoblast differentiation. [17,18] Moreover, some of the scaffolds were reinforced through addition of a proper amount of gelatin, [35] in order to modulate strontium release. Viability and activity of bone cells were evaluated using cocultures of osteoblasts and osteoclasts.…”
Section: Introductionmentioning
confidence: 99%
“…[ 40,41 ] Silk fibers, hydroxyapatite, and gelatin have all been utilized as reinforcements for mechanical behavior of a hydrogel. [ 42–44 ] This approach is particularly reliant on maintaining a polymer's ability to be processable with the additive reinforcement and biocompatible for human use. Given PEGDMA may be insufficient in terms of its strength for “permanent” replacement of articular cartilage, one such polymer that is both biocompatible and processable as a hydrogel for this particular application is poly(vinyl alcohol).…”
Section: Introduction Of Synthetic Hydrogelsmentioning
confidence: 99%
“…In brief, PCL scaffolds were dehydrated by freeze‐drying, sputter‐coated with a thin layer of gold, and then imaged at an accelerating voltage of 10 kV. Average porosities of PCL scaffolds fabricated from different ratios of PCL to porogen were evaluated by a fluid replacement method as described previously . The mechanical properties of PCL scaffolds were determined by the stress–strain mechanical analysis which was carried out using a mechanical testing system (GT‐TCS2000, GOTECH, China) equipped with a computerized control and measurement system.…”
Section: Methodsmentioning
confidence: 99%
“…Average porosities of PCL scaffolds fabricated from different ratios of PCL to porogen were evaluated by a fluid replacement method as described previously. [39,40] The mechanical properties of PCL scaffolds were determined by the stress-strain mechanical analysis which was carried out using a mechanical testing system (GT-TCS2000, GOTECH, China) equipped with a computerized control and measurement system. Samples were prepared via a special mold with dimensions of 10 mm × 5 mm (diameter × thickness).…”
Section: Preparation and Characterization Of Biomimetic Macroporous Smentioning
confidence: 99%